Total Contact Cast after Sole Free Flap Reconstruction for Early Ambulation - Yutaro Yamashita; Yoshiro Abe; Mayu Bando; Shunsuke Mima; Hiroyuki Yamasaki; Shinji Nagasaka; Kazuhide Mineda; Ichiro Hashimoto (Archives of Plastic Surgery)
Background Free flap reconstruction can be performed in patients with chronic limb-threatening ischemia (CLTI). However, early walking training may increase the risk of wound dehiscence and prolong hospitalization. Total contact cast (TCC) treatment effectively addresses diabetic plantar ulcers by immobilizing the foot and distributing weight away from the ulcer area. This study aimed to assess the effect of postoperative TCC use on early limb loading and hospital stay in patients with CLTI with free flaps.